Chronic pain, chronic stress and substance use: overlapping mechanisms and implications - Schaffer, J.; Fogelman, N.; Seo, D.; Sinha, R. (Frontiers in Pain Research, 2023)
Chronic pain is among the most common reasons adults in the U.S. seek medical care. Despite chronic pain's substantial impact on individuals' physical, emotional, and financial wellness, the biologic underpinnings of chronic pain remain incompletely understood. Such deleterious impact on an individuals' wellness is also manifested in the substantial co-occurrence of chronic stress with chronic pain. However, whether chronic stress and adversity and related alcohol and substance misuse increases risk of developing chronic pain, and, if so, what the overlapping psychobiological processes are, is not well understood. Individuals suffering with chronic pain find alleviation through prescription opioids as well as non-prescribed cannabis, alcohol, and other drugs to control pain, and use of these substances have grown significantly. Substance misuse also increases experience of chronic stress. Thus, given the evidence showing a strong correlation between chronic stress and chronic pain, we aim to review and identify overlapping factors and processes. We first explore the predisposing factors and psychologic features common to both conditions. This is followed by examining the overlapping neural circuitry of pain and stress in order to trace a common pathophysiologic processes for the development of chronic pain and its link to substance use. Based on the previous literature and our own findings, we propose a critical role for ventromedial prefrontal cortex dysfunction, an overlapping brain area associated with the regulation of both pain and stress that is also affected by substance use, as key in the risk of developing chronic pain. Finally, we identify the need for future research in exploring the role of medial prefrontal circuits in chronic pain pathology. Critically, in order to alleviate the enormous burden of chronic pain without exacerbating the co-occurring substance misuse crisis, we emphasize the need to find better approaches to treat and prevent chronic pain.